Polymorphism of BGN gene (g.77807325 G>C) and its association with fatty acid and carcass characteristics of Indonesian meat lamb - Amin, M. F.; Sumantri, C.; Arief, I. I.; Jayanegara, A.; Listyarini, K.; Harahap, R. S.; Gunawan, A. (Diponegoro University, 2024)
Fatty acid content and carcass characteristics are two meat quality traits consumers choose to ob tain healthy and high-quality lamb. Genetic improvement of fatty acid content and carcass characteris tics in sheep is important to increase the public appeal of lamb meat. The Biglycan gene (BGN) is a gene that functions to regulate the growth and maintenance of connective tissues, such as bone and cartilage. This study examined the polymorphism of the BGN gene to get a deeper understanding of the correlation between fatty acid content and carcass traits in Indonesian sheep. The PCR-RFLP ap proach was used to detect polymorphism in the BGN gene in meat samples obtained from the longissi mus dorsi region of 115 rams aged between 10 and 12 months. The General Linear Model (GLM) was used test to analyze genotyping through association studies between genotypes and phenotypic attrib utes. The results indicated that the carcass' fatty acid composition, including tridecanoic acid (C13:0), arachidonic acid (C20:4n-6), and polyunsaturated fatty acids (PUFA), as well as the BGN gene with SNP point g. 77807325 G>C (GG and CC genotypes), were significantly (P<0.05) related to these traits. Genotype GG was more associated with carcass percentage traits than other genotypes, whereas genotype CC was best associated with carcass length traits. The BGN gene with SNP point g. 77807325 G>C can be a potential genetic marker for selecting fatty acid (tridecanoic acid C13:0), pol yunsaturated fatty acid (PUFA), arachidonic acid), carcass percentage, and carcass length in sheep meat in Indonesia.